ナンキョクカイ ヒョウメンスイ ノ Ca Sr I Mo ノ ソクテイ - 菅原, 健; スガワラ, ケン; 寺田, 喜久雄; テラダ, キクオ; 川崎, 暢子; カワサキ, ノブコ; 岡部, 史郎; オカベ, シロウ; SUGAWARA, Ken; TERADA, Kikuo; KAWASAKI, Nobuko; OKABE, Shiro (国立極地研究所, 1959)
P(論文) departmental bulletin paper